Consensus report on the radiological management of patients with gastrointestinal stromal tumours (GIST): recommendations of the German GIST Imaging Working Group - Kalkmann, Janine; Dinter, Dietmar; Fink, Christian (Cancer imaging, 2012)
The aim was to reach consensus in imaging for staging and follow-up as well as for therapy response assessment in patients with gastrointestinal stromal tumours (GIST). The German GIST Imaging Working Group was formed by 9 radiologists engaged in assessing patients with GIST treated with targeted therapy. The following topics were discussed: indication and optimal acquisition techniques of computed tomography (CT), magnetic resonance imaging (MRI) and positron emission tomography (PET)/CT; tumour response assessment considering response criteria and measurement techniques on CT, MRI and PET/CT; result interpretation; staging interval and pitfalls. Contrast-enhanced CT is the standard method for GIST imaging. MRI is the method of choice in case of liver-specific questions or contraindications to CT. PET/CT should be used for early response assessment or inconclusive results on morphologic imaging. All imaging techniques should be standardized allowing a reliable response assessment. Response has to be assessed with respect to lesion size, lesion density and appearance of new lesions. A critical issue is pseudoprogression due to myxoid degeneration or intratumoural haemorrhage. The management of patients with GIST receiving a targeted therapy requires a standardized algorithm for imaging and an appropriate response assessment with respect to changes in lesion size and density.
Published online 2012 May 7
Gesehen am 18.06.2018